2015
DOI: 10.1111/apm.12385
|View full text |Cite
|
Sign up to set email alerts
|

Secretion, blood levels and cutaneous expression of TL1A in psoriasis patients

Abstract: TL1A is a TNF-like cytokine which has been shown to co-stimulate TH1 and TH17 responses during chronic inflammation. The expression of this novel cytokine has been investigated in inflammatory disorders like rheumatoid arthritis and inflammatory bowel disease, but little is known about expression and induction in psoriasis. Indeed, the pathogenesis in psoriasis is still not fully understood and it is speculated that cytokines other than TNF-α are important in subsets of patients. Also, for patients with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that both protein expressions and mRNA transcripts of TL1A and DR3 were increased in psoriatic lesions (Bamias et al, 2011). Serum TL1A levels were significantly elevated in patients with psoriasis but not in patients with atopic dermatitis and health control, and the high serum TL1A levels were decreased after treatment (Li et al, 2014;Pedersen et al, 2015). Li et al detected the expression of DR3 in PBMCs of patients with psoriasis and found that there was a positive correlation between the percentage of DR3 + CD8 + and DR3 + CD14 + cells and the PASI scores in patients with psoriasis .…”
Section: The Role Of the Ox40:ox40l Pathway In Psoriasismentioning
confidence: 95%
“…Previous studies have shown that both protein expressions and mRNA transcripts of TL1A and DR3 were increased in psoriatic lesions (Bamias et al, 2011). Serum TL1A levels were significantly elevated in patients with psoriasis but not in patients with atopic dermatitis and health control, and the high serum TL1A levels were decreased after treatment (Li et al, 2014;Pedersen et al, 2015). Li et al detected the expression of DR3 in PBMCs of patients with psoriasis and found that there was a positive correlation between the percentage of DR3 + CD8 + and DR3 + CD14 + cells and the PASI scores in patients with psoriasis .…”
Section: The Role Of the Ox40:ox40l Pathway In Psoriasismentioning
confidence: 95%
“…Macrophages overexpressing TL1A promoted secretion of TNF-α and IL-1β ( 26 ). Monocytes secreted TL1A in response to stimulation by immune complexes, leading to enhanced T cell responses ( 5 , 27 ). In inflammatory bowel disease, TL1A is produced in the intestinal lamina propria of macrophages in patients with Crohn’s disease ( 23 ).…”
Section: Biologic Functions Of Tl1amentioning
confidence: 99%
“…Psoriasis is a common inflammatory skin disease characterized by thickened, scaly, red skin patches ( 73 ). TL1A is predominantly expressed in psoriatic lesions, particularly in infiltrating inflammatory cells, keratinocytes and vascular cells ( 27 , 74 ). TL1A promotes production of IL-17, which induces granulocyte colony-stimulating factor (G-CSF) and chemokine ligand 20 (CCL20) and recruits large number of neutrophils to damaged joints, leading to early inflammation.…”
Section: Association Between Tl1a and Inflammatory Autoimmune Diseasesmentioning
confidence: 99%
“…DR3 and TL1A expression is found in skin lesions, but not in healthy skin areas of patients with active psoriasis, indicating a pathogenic role. Immunohistochemistry and gene expression analysis of psoriatic skin lesions suggest TL1A expression by numerous immune and nonimmune cells, for example, keratinocytes, endothelial cells, neutrophils, lymphocytes, and monocytes .…”
Section: Dr3 In Chronic Inflammatory Diseasementioning
confidence: 99%